Um regaste conceitual da compreensão da Igreja como Povo de Deus à luz da Lumen Gentium e sua aplicação no Doc. 105 da CNBB - Frezzato, Anderson (2020)
This research aims to present the notional understanding of the Church as People of God and its application in the Document 105 “Lay Christians in the Church and Society” of the National Conference of Bishops of Brazil. This document, published in 2016, reflects on lay protagonism under the light of the ecclesiology of the Second Vatican Council. This is an effort by the Church in Brazil to receive and update the conciliar proposals. On that occasion, the Conciliar Fathers broke with an overly closed and juridical ecclesiological view, to affirm, propelled by some renewing movements of theological work, that the Church is first and foremost a mystery whose origin is in One-Triune God and a historical concretization. it is made as a people in the election of Israel as the People of God. And not only, but also new People when so many others become disciples and missionaries of Jesus, gathered through the Church. The Church is then the People of God, community of disciples of Jesus, community of equals. Everyone can be part of God's People through baptism and through this basic sacrament, everyone has the same dignity inside and outside the community of faith. What differentiates them is how they render service to the Kingdom of God. The purpose of the research is to show that Doc. 105 is an instrument capable of, if studied and applied, producing greater awareness of belonging to the People of God and the engagement in pastoral life. However, much remains to be done to bring the conciliar spirit and its prospects of openness and dialogue to the Church of the present time. There are many current difficulties, as the field research shows, such as the laity's poor formation, lack of knowledge about the conciliar event, and the inability of the laity to know how to cite any document of the Council. Clericalism is still a major hindrance to the renewal of the ecclesial community and must be fought, back especially by lay and lay Christians. It is shown throughout the development of the research that lay Christians are understood as subjects and perform actions ad intra or ad extra Ecclesia with autonomy and freedom. They are not mere representations; they are the church indeed. They are not only present in the ecclesial community, but even more so in society, where they are promoters of transformative actions. Today, thanks to divine inspiration in the Church, we can count on the pontificate of Pope Francis who through words and attitudes has brought to light the spirit of conciliar aggiornamento, inviting the Church to be in a constant posture for departure, going, in them joy for the mission, aiming to meet the other, especially the poorest. Francis has led the Church to become more conciliatory, especially when he appeals to ordained ministers to have a penchant for working with the sheep entrusted to them, assuming in their own lives uhe realities of each one to the point of smelling like them